DISC HERNIATIONS AND CAUDA EQUINA COMPRESSION IN UNILATERAL AND BILATERAL ARTICULAR FUSION LUMBOSACRAL TRANSITIONAL ANATOMY TYPES - Matveeva, Niki; Cabukovska, Jasmina; Papazova, Mairja; Zivadinovik, Julija; Zafirova, Biljana; Bojadzieva, Biljana; Trpkovska, Biljana (Journal of Morphological Sciences; Vol 1 No 1 (2018): JMS, 2018)
Background: The relationship between different lumbosacral transitional vertebra (LSTV) types, disc herniations and  neural structures compromise has been sporadically reported. Objectves: The objectives of this study was to evaluate the relationship between articular fusion LSTV types, disc herniations and  neural structures compromise. Material and Methods: A total of 92 patients with lumbosacral radicular syndrome who underwent MRI examination of the lumbar spine were included in the study. All patients had at least one evaluated disc herniation at the last three mobile levels. These patients were separated in two groups. Study group comprised 58 patients who presented with LSTV (articular fusion type based on Castellvi classification). Additionaly this group was separated in two subgroups; 25 patients with unilateral  and 33 of them with bilateral articular fusion LSTV type. Thirty four patients without LSTV were assigned to the control group. Results: There were significantly more disc herniations (92% vs 73.5%, p=.03) and more severe cauda equine compression (12% vs 5.9%) at the level of transition in the  LSTV unilateral articular fusion subgroup compared to the control group. At the adjacent proximal level significantly more disc herniations (93.9% vs 73.5%, p=.03) and more severe cauda equina compression (51.5% vs 14.7, p=.012) was observed in the LSTV bilateral articular fusion subgroup compared to the control group. Conclusion: In conclusion, altered morphology and biomechanics in articular fusion LSTV types provoke disc herniations and severe cauda equina compression to occur more frequently. Key words:  spine; lumbosacral transitional vertebra; MRI; disc herniation; cauda equina